France : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
France's recent economic performance has been distinctly positive, supported by policy reforms over a number of years and a favorable monetary and external environment. The fiscal deficit has narrowed significantly in recent years. Improving long-term economic performance depends crucially on significant reductions in France's high tax burden. Effective expenditure control over the medium term will depend on reforms of the civil service and of the major transfer programs, notably pensions. There has been notable progress in privatization, but less in opening up key network sectors.